PERANCANGAN SISTEM KONTROL KETINGGIAN AIR PADA TANAMAN HIDROPONIK DENGAN METODE LOGIKA FUZZY MAMDANI - Muhammad Fajar Ramadhan; Sholihin (CV. Multi Kreasi Media, 2023)
Hydroponic plants have become a conversation among millennials. Hydroponic plants are an alternative farming system for city dwellers because they do not require extensive soil and space media. However, how to grow hydroponics is still difficult for ordinary people. Hydroponic plants should not be given direct sunlight but must be moved to a place that can protect these plants from direct sunlight. The use of water in hydroponic plants is also a very important issue. Water can be reduced due to evaporation from sunlight so that hydroponic plants that use reservoirs must be continuously filled with sufficient water. This of course makes it difficult for the plant owner because of the busyness of the plant owner himself. With this problem in mind, a tool design was made to control the volume of water in the reservoir using fuzzy technology. The fuzzy system was made to meet the needs of hydroponic plant owners with a holding tank method so that water remains at a threshold where plant roots can absorb water. The use of a pump may be an alternative, but the achievement of thresholds and efficiency may not be achieved. The system proposed in this study is the control of a water pump to circulate water with two sensors so that the water in the reservoir will always be right at the threshold.